Arrangements for upgrading the Maghrebian Tunisia, Morocco ‎and Algeria SMEs.‎ - AIT SI SAID, Radia; BOUZAR , Chabha (Dirassat Journal Economic Issue, 2016)
The new context of economic liberalization and globalization is marked by deep and complex rapid change. In this new context, each Maghreb country must prepare and implement a comprehensive program of restructuring and upgrading. The requirement for the Maghreb countries to integrate into the global economy has to go through the introduction of a competitive market economy through upgrading of their industries. The implementation of an upgrading program in the Maghreb countries which have production structures and levels of economic development calls for several different reflections. Indeed , the study programs of upgrading Maghreb SMEs , if it can find common foundations, also reveals significant differences in their institutional structures and roles of governments that could explain the significant differences observed in terms impact . The purpose of this article, on the one hand, is to sketch an overview of the North African SMEs, its characteristics, structural weaknesses and the unsuitability of the environment business need. On the other hand, it is to expose the role and the necessity of upgrading in local production, modernizing management and information systems and promoting industrial competitiveness.